Una propuesta de formalización del principio de conservación de la energía desde la perspectiva de Mayer - Agudelo Restrepo, Christian Camilo; Palacio Muñoz, Óscar David; Londoño Zuleta, Julián Andrés; Aguilar Mosquera, Yirsen (Revista Científica, 2011)
In the analysis made in research, is notoriously difficult, for several students in theconceptualization and implementation of the principle of conservation of energy, amongother highlights failure to distinguish between the concept of work and the concept ofenergy, which leads to circularity when trying to explain any phenomenon by applyingthese concepts. As an alternative proposal raises a recontextualization of that principle, byanalyzing historical epistemology of the work (Forces of Inorganic Nature, Mayer, 1973),arguing that their particular way of formalizing the Principle of Conservation of Energy, noonly allows a redefinition of the concepts involved, but also allows us to suggestalternative routes to teaching teaching this Principle of Conservation.The proposal is structured recontextualization raised from the construction and applicationof a series of instruments (these arise from the approach of Mayer) to inquire aboutalternative ideas and seek the use of new models that explain the phenomenon. Accordingto the analysis of the results, we conclude that energy, to be under the cause-effect isachieved through induction and maintenance of convertibility of it. Given the variousdifficulties in teaching, it became necessary to design teaching strategies based on thehistory and epistemology can be considered viable teaching and learning of physics.